ANALISIS PERBANDINGAN PROSES FONOLOGIS: IBDAL DAN I’LAL DALAM BAHASA ARAB DAN PELULUHAN DALAM BAHASA INDONESIA - Tika Muslikha Risqiani (AT-TAKLIM: Jurnal Pendidikan Multidisiplin, 2025)
This study aims to analyze and compare three significant phonological processes: ibdāl and i‘lāl in Arabic and consonant weakening (commonly referred to as peluluhan) in Indonesian. These processes represent systematic sound changes that occur to simplify pronunciation in specific morphological or phonetic contexts. Employing a descriptive qualitative approach with a library research method, this study collects data from scholarly literature on Arabic and Indonesian linguistics. The analysis involves identifying the structural characteristics of each process, comparing their phonological patterns, and evaluating their purposes and implications in word formation. The findings reveal that ibdāl is a broader process involving the substitution of one consonant for another, applicable to both regular and weak consonants. I‘lāl, on the other hand, is a more specific subset of ibdāl, dealing exclusively with weak letters (alif, waw, ya’) and governed by strict morphological rules. In contrast, consonant weakening in Indonesian is a phonetic adaptation that occurs during affixation, aiming to produce smoother pronunciation without being bound by rigid morphological structures. Despite originating from different language families and grammatical systems, all three processes serve a common phonological goal: facilitating articulation and maintaining speech fluency.